ANALISIS DETERMINANT FACTOR EFEKTIVITAS STRATEGI PENANGANAN PENCEMARAN AIR DI SUNGAI MOJOKERTO - Fasich Rahman Hendyarta Permana; Kalvin Edo Wahyudi (Halu Oleo University, 2025)
This research aims to analyse the determining factors that influence the effectiveness of strategies for managing water pollution in the Sadar River, conducted by the Environmental Agency of Mojokerto Regency. The background of this study is the high level of pollution caused by domestic and industrial waste, which affects environmental quality and public health. The research employed a descriptive qualitative approach using interviews, observations, and documentation techniques. The theory of strategy effectiveness proposed by Sutrisno (2010) served as the framework. The findings include four main indicators: Organisational Characteristics, Environmental Characteristics, Worker Characteristics, and Policy Characteristics. The results show that the organisational structure has complied with Standard Operating Procedures and supported the strategy; however, there are still limitations in employee competency qualifications and a lack of support and involvement from the private sector. Moreover, industry compliance remains low. In conclusion, it is necessary to improve human resource capacity, enforce regulations more strictly, and enhance cross-sector collaboration to achieve optimal water pollution control.